Characteristics of Internet, Smartphone, and Social Media Usage among Generation Z in South Jakarta after the COVID-19 Pandemic - Nurbaiti Nurbaiti (Journal of Health Sciences and Epidemiology, 2023)
The amount of internet usage has increased following the COVID-19 pandemic in 2020. In order to reduce the transmission of COVID-19, the government implemented a policy mandating remote learning. Generation Z finds learning online at home enjoyable, and there is a growing trend of using the Internet for educational purposes. This study examined the characteristics of Internet, smartphone, and social media usage among Generation Z during the COVID-19 pandemic, which is expected to diminish by early 2022. A descriptive study was conducted, and data was collected through a survey of 50 respondents belonging to the Gen Z demographic, specifically aged 12-15 years, in South Jakarta. The research variables encompassed internet usage, smartphone usage, social media usage, and information regarding internet usage. The data analysis performed univariate analysis. The research results showed that the characteristics of Gen Z in South Jakarta are spending between 1 and 8 hours on social media. Most of them owned and used smartphones. Popular platforms for Gen Z were YouTube, TikTok, WhatsApp, Instagram, and Telegram. They posted photos, videos, and stories on social media but rarely trusted the information there. WhatsApp groups were also used for the learning process. Gen Z got information about internet usage from the people around them. To prevent the risks of excessive use of the Internet, smartphones, and social media, education for Gen Z still needs to be a concern.